2010
DOI: 10.1021/ja105306s
|View full text |Cite
|
Sign up to set email alerts
|

Stereomutation of Pentavalent Compounds: Validating the Berry Pseudorotation, Redressing Ugi’s Turnstile Rotation, and Revealing the Two- and Three-Arm Turnstiles

Abstract: A general reaction mechanism describes the qualitative change in chemical topology along the reaction pathway. On the basis of this principle, we present a method to characterize intramolecular substituent permutation in pentavalent compounds. A full description of the geometry around five-coordinate atoms using internal coordinates enables the analysis of the structural changes along the stereomutational intrinsic reaction coordinate. The fluxional behavior of experimentally known pentavalent phosphoranes, si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
156
2
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(176 citation statements)
references
References 78 publications
12
156
2
6
Order By: Relevance
“…90 Indeed, it 65 is only recently that definitive computational and experimental results have appeared that shed light on the elusive details of this part of the mechanism (see the section on the modern mechanstic interpretation for the Wittig reaction). 40,91 In any case, it is the origin of the stereoselectivity induced in the OPA intermediate 70 that is of greatest interest since this stereochemistry is retained exactly in the alkene product after decomposition, and this was the primary focus in the work of Vedejs and co-workers.…”
Section: Vedejs Cycloaddition Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…90 Indeed, it 65 is only recently that definitive computational and experimental results have appeared that shed light on the elusive details of this part of the mechanism (see the section on the modern mechanstic interpretation for the Wittig reaction). 40,91 In any case, it is the origin of the stereoselectivity induced in the OPA intermediate 70 that is of greatest interest since this stereochemistry is retained exactly in the alkene product after decomposition, and this was the primary focus in the work of Vedejs and co-workers.…”
Section: Vedejs Cycloaddition Mechanismmentioning
confidence: 99%
“…90 50 Recently, Lamertsma & co-workers have shown that permutation of ligands in trigonal bipyramidal species may occur in a single step by processes that are comprised of multiple consecutive Berry pseudorotations. 91,101,102 González, López-Ortiz & co-workers have shown that one or more of these single 55 step mechanisms is highly likely to operate in the interconversion (stereomutation) of OPAs very similar to those produced in typical Wittig reactions. 40 Although there exists at least one example of a Wittig reaction of a chiral ylide in which the chirality of the phosphorus centre is retained in the phosphine 60 oxide product, 79 the implication of the results of González, López-Ortiz & co-workers is that retention of configuration at phosphorus is unlikely in any Wittig reaction in which OPA stereomutation is faster than OPA decomposition.…”
Section: Oxaphosphetane Structure and Cycloreversion Mechanismmentioning
confidence: 99%
“…It should be noted here that the very recent DFT calculations of the fluxional behavior of experimentally known pentavalent molecules have suggested the equivalence of the turnstile rotation with the Berry pseudorotation. This suggestion is based on identification of three principal mechanisms by which the substituents interchange can be achieved (Berry pseudorotation, threefold cyclic permutation, and half-twist axial-equatorial interchange) [27]. ( Figure 3).…”
Section: Chiral Phosphoranes As Reactive Intermediatesmentioning
confidence: 99%
“…3 Such intermediates can undergo a fast intramolecular ligand exchange process, termed Berry pseudorotation,4,5 that may have a significant effect on the outcome of the reaction. 6,7 However, in the case of the Appel reaction conditions, 8 while the involvement of chloro-and alkoxy-phosphonium species is well established, 9,10,11 the extent of participation of pentaco-ordinate phosphorane intermediates is less clear.…”
Section: H 2 / Pd-c 2 (I) (Cocl)mentioning
confidence: 99%